2015
DOI: 10.4067/s0034-98872015000200010
|View full text |Cite
|
Sign up to set email alerts
|

Avances en el tratamiento de cáncer de próstata resistente a la castración: énfasis en nuevas terapias hormonales

Abstract: (Rev Med Chile 2015; 143: 223-236)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
1
0
2
Order By: Relevance
“…Tan concluded that there is a need to improve on this survival benefit, since, with the standard treatment, the relapse-free survival among responders is often short (6 months) and patients often exhibit cancer progression, which leads to mortality. There is a need to develop less toxic drugs that would significantly improve survival ( 85 , 86 ). OV, when used as supportive therapy, decreased the toxicity of docetaxel and improved patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Tan concluded that there is a need to improve on this survival benefit, since, with the standard treatment, the relapse-free survival among responders is often short (6 months) and patients often exhibit cancer progression, which leads to mortality. There is a need to develop less toxic drugs that would significantly improve survival ( 85 , 86 ). OV, when used as supportive therapy, decreased the toxicity of docetaxel and improved patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Тем не менее стабильный контроль РПЖ не может быть полностью достигнут только применением андрогендепривационной терапии в связи с развитием в конечном итоге кастрационно-резистентной фазы заболевания. В таком случае пациенты умирают в течение 1-2 лет с начала признаков прогрессирования заболевания [8]. Тем не менее андрогендепривационная терапия у большинства больных является эффективной и может проводиться при любых формах РПЖ [5,6].…”
Section: Introductionunclassified
“…Тем не менее стабильный контроль РПЖ не может быть полностью достигнут только при-менением андрогендепривационной терапии в связи с развитием в конечном итоге кастрационно-рези-стентной фазы заболевания. В таком случае пациенты умирают в течение 1-2 лет с начала признаков про-грессирования заболевания [8]. Однако андрогенде-привационная терапия у большинства больных РПЖ эффективна и может проводиться при любых формах заболевания [5,6] Диагностика и лечение опухолей мочеполовой системы.…”
unclassified